AdSafe Analyzer: A Rule-Based Compliance Checker for Thai Healthcare Advertising - Chotikunnan, Phichitphon; Khotakham, Wanida; Imura, Pariwat; Chotikunnan, Rawiphon; Boonkrong, Pichit; Thongpance, Nuntachai; Suksuwan, Paweena (Engineering, Technology & Applied Science Research, 2026)
Healthcare advertising is subject to strict regulatory and ethical standards to prevent misleading claims, which also applies in the digital environment. This study presents AdSafe Analyzer (ASA), which is a web-based, rule-driven platform designed to support regulatory compliance in healthcare and cosmetic advertising in Thailand. ASA functions as a pre-publication screening tool, evaluating advertising content against a standardized set of keywords derived from regulatory guidelines, categorizing expressions as legal, conditionally permitted, or prohibited. The system utilizes a phrase-level reverse-search pattern-matching technique with text normalization, enabling real-time identification of restricted expressions without relying on intricate language models. The system was evaluated using curated datasets, comprising restricted phrases, sentence-level instances, and a negative control corpus of conforming advertisements, demonstrating perfect recall, precision, and F1-score values of 1.00, with no False Positives (FPs) observed under the tested conditions. Therefore, by providing an efficient and transparent pre-publication compliance check, ASA mitigates regulatory risk and promotes responsible communication in healthcare advertising. A live prototype of the system is available at http://researchbme.rsu.ac.th/ASA_V1/index.html.